Pengaruh Brand Ambassador Dan Kualitas Produk Terhadap Keputusan Pembelian Sunscreen Azarine Di Kota Bekasi - Budi Lestari, Fitria; Chairani, Ridfa (JAMBIS : Jurnal Administrasi Bisnis, 2024)
The phenomenon in this research is due to a decrease in the level of sales of Azarine sunscreen products in 2022 which is caused by several factors. This research aims to find out how much influence brand ambassadors and product quality have on purchasing decisions for Azarine sunscreen in Bekasi City. This research uses a descriptive quantitative method approach. The samples in this research were consumers who had purchased and used Azarine sunscreen, especially respondents who lived in Bekasi City with a total sample of 120 respondents. Data analysis uses multiple linear regression. This research shows that brand ambassador (X1) has a significant influence on purchasing decisions (Y). Product quality (X2) has a significant effect on purchasing decisions (Y). Brand ambassador (X1) and product quality (X2) have a significant influence on purchasing decisions (Y) by 61% and the remaining 39% is influenced by other variables not examined in this research.